Compositionally tailored order-disorder of cation-anion sublattices in Cu2Te1-xSx solid solution thermoelectric materials. (15th April 2023) - Su, Hong; Lu, Ping; Zhu, Chenxi; Qiu, Wujie; Qiu, Xianxiu; Zhao, Kunpeng; Lu, Xiaoyue; Wei, Yuyu; Shi, Xun; Chen, Lidong; Xu, Fangfang
Abstract: High performance thermoelectric Cu2 Te1- x S x solid solutions can surprisingly be formed over a wide compositional range even with big atomic size difference between S and Te. The Cu sublattice has been found to be partially ordered and even shows amorphous substructures in some compositions, while S/Te is considered to form a chemically disordered yet crystalline sublattice. However, precise order-disorder configurations of cation-anion sublattices and their evolution upon compositional change still remain unclear. Meanwhile, the appearance of diffuse reflections on the electron diffraction patterns suggests occurrence of short-range order whose structures are not yet solved. Here, atomic structures of Cu2 Te1- x S x ( x  = 0.1, 0.2, 0.4, 0.5, 0.6 and 0.8) have been investigated by transmission electron microscopy in both real and reciprocal spaces. The high-angle annular dark field atomic imaging indicates an approximate hexagonal stacking for S/Te atoms in all solution compositions. However, location of Cu atoms in numerous interstices of the chalcogen sublattice varies by S/Te atomic ratio, leading to change in order-disorder configurations of Cu or even nanoscale phase separation. Diffuse scattering with different geometries are identified to arise from chemical short-range order in forms of sulphur-rich atomic layers on (0001) and lath-like tellurium aggregation on {10-10}. The as-observed compositionally tailored solid solution structures and short-range order structures are found to be strongly correlated to the electron and phonon transportation in Cu2 Te1- x S x . The present work indicates a promising strategy for designing solid solutions having large atomic-size mismatch which may generate abundant order/disorder atomic configurations hence greatly improve the thermoelectric properties. Graphical abstract: Image, graphical abstract